What Is the Role of Resilience and Coping Strategies on the Mental Health of the General Population during the COVID-19 Pandemic? Results from the Italian Multicentric COMET Study - Gaia Sampogna; Valeria Del Vecchio; Vincenzo Giallonardo; Mario Luciano; Umberto Albert; Claudia Carmassi; Giuseppe Carrà; Francesca Cirulli; Bernardo Dell’Osso; Giulia Menculini; Mariagiulia Nanni; Maurizio Pompili; et al. (Brain Sciences, 2021)
The effects of the COVID-19 pandemic on mental health are now well documented, however, few studies have been focused on the role of coping strategies and resilience in counterbalancing these detrimental effects. Data are derived from the COvid Mental hEalth Trial (COMET), a national multicentric trial carried out in the Italian general population. The final sample consisted of 20,720 participants, 53.1% (n = 11,000) of the sample reported low levels of resilience. Adaptive coping strategies and resilience levels did not have any significant protective impact on the levels of depressive, anxiety, and stress symptoms. Only self-distraction was a risk factor for poor mental health (Beta Coefficient, B = 0.1, 95% Confidence Interval, CI: 0.003 to 0.267 for stress symptoms; B = 0.2; 95% CI: 0.077 to 0.324 for anxiety symptoms and B = 0.2, 95% CI: 0.105 to 0.382 for depressive symptoms). High levels of resilience were predicted by adaptive coping strategies, such as acceptance (B = 1.8, CI 95% = 1.4–2.7). Exposure to the different weeks of lockdown, being infected by COVID-19, and being a healthcare professional did not influence the levels of resilience. Our findings should be carefully considered, since the low levels of resilience may represent the missing link between the pandemic and the current increase in mental health problems.